First record of the endemic anthozoan Spinimuricea klavereni (Carpine & Grasshoff 1975) (Cnidaria, Anthozoa, Plexauridae) in the Adriatic Sea - Mačić, Vesna; Trainito, Egidio; Petović, Slavica (2021)
We present the first record of the endemic Mediterranean anthozoan Spinimuricea klavereni (Carpine & Grasshoff 1975) (Cnidaria, Anthozoa, Plexauridae) for the Adriatic Sea (Boka Kotorska bay, Montenegro). A density of 0.72 colonies m-2 could be measured in the area, which was com-pared with the scant available data in the literature. Having in mind that this species is very rare and endemic for the Mediterranean, it is important to increase our knowledge on its distribution and biology in order to better assess its ecological role, the pending threats and the need for specific conservation measures.
Prikazan je prvi nalaz endemičnog sredozemnog žarnjaka Spinimuricea klavereni (Carpine & Grasshoff 1975) (Cnidaria, Anthozoa, Plekauridae) za Jadransko more (Bokokotorski zaliv, Crna Gora). Dobijeni rezultati i izmjerena gustina od 0,72 kolonije m-2 su uspoređeni s oskudnim podacima dostupnim u literaturi. Imajući u vidu da je ova vrsta vrlo rijetka i endemska za Sredozemno more, važno je poboljšati znanje o njenoj distribuciji i biologiji kako bismo bolje procijenili njenu ekološku ulogu, prijetnje i potrebu za određenim mjerama zaštite.
Bibliografija: str. 79-81.
Summary ; Sažetak.
Keywords: Žarnjaci -- Spinimuricea klavereni -- Endemi; Bokokotorski zaljev -- Crna Gora -- Jadransko more